2015
DOI: 10.3823/1707
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of CPR Workshop on the Nurses’ Level of Knowledge and Skill

Abstract: Background & Aim: The significance of cardiopulmonary resuscitation (CPR) used by nurses in their professional success has been discussed. The aim of this study is to determine the effect of workshop training method on the nurses' knowledge and skill of CPR. Material & Methods: This quasi-experimental study was conducted on 140 nurses of Zabol University of Medical Science in a single group (before and after and three months after the training workshop) .The data collection tool was the knowledge questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…The results were similar for practical and theoretical skills, while the score of practical skills significantly decreased after two years (8). The low level of nurses' knowledge and skills in CPR, effectiveness of training in knowledge promotion, and necessity of regular CPR training courses for maintaining the nurses' knowledge and skills are the most important findings reported by Shahrakivahed et al in 2015 (22), which are in agreement with our results.…”
Section: Discussionsupporting
confidence: 93%
“…The results were similar for practical and theoretical skills, while the score of practical skills significantly decreased after two years (8). The low level of nurses' knowledge and skills in CPR, effectiveness of training in knowledge promotion, and necessity of regular CPR training courses for maintaining the nurses' knowledge and skills are the most important findings reported by Shahrakivahed et al in 2015 (22), which are in agreement with our results.…”
Section: Discussionsupporting
confidence: 93%
“…A study conducted in Iran confirmed that regular training and workshops can be useful and effective to help retain nurses’ knowledge and skills. 22 Other CPR researchers point out that when a lengthy interval occurs between the periodic CPR, refresher-training courses should be provided to all the practising nurses as a part of their continuous professional development. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Other authors have conversely reported that nurses working in high-risk areas such as Intensive Care Unit (ICU) and nurses who work continuously in close contact with patients are more motivated to maintain their competence in CPR than other health care professionals. 22 Unlike these authors, nurses working in ICU were not included in our study owing to a lack of ICU in district hospitals in Botswana.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, holding CPR retraining workshop can increase the nurses' competency in CPR. [ 16 ] Due to the passage of time and forgetting the training materials, retraining the nursing students in CPR is stressed. [ 42 ] Hence, it is recommended to use the up-to-date CPR guidelines for student education.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 15 ] Moreover, CPR drugs should be administered intravenously, but intraosseous infusion is commonly applied when there is no access to veins and is preferable to intracranial infusion. [ 5 ] After confirming the success of CPR, it is recommended that the induced hypothermia be used at a temperature of 32°C–34°C within a 12–24-h interval and reheating after 24 h.[ 16 17 ]…”
Section: Introductionmentioning
confidence: 99%